2015
DOI: 10.2337/dc16-s014
|View full text |Cite
|
Sign up to set email alerts
|

11. Children and Adolescents

Abstract: TYPE 1 DIABETESThree-quarters of all cases of type 1 diabetes are diagnosed in individuals ,18 years of age. The provider must consider the unique aspects of care and management of children and adolescents with type 1 diabetes, such as changes in insulin sensitivity related to physical growth and sexual maturation, ability to provide self-care, supervision in the child care and school environment, and neurological vulnerability to hypoglycemia and hyperglycemia in young children, as well as possible adverse ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(16 citation statements)
references
References 78 publications
0
14
0
2
Order By: Relevance
“…Unfortunately, this confluence of issues often results in deteriorating glycemic control. International data have identified significant shortfalls as only about 14% patients with T1DM aged 11-18 years actually achieve glycated hemoglobin (HbA1c) levels of b7.5% (Dunger, 2017;Maahs et al, 2014;Miller et al, 2015) which is the consensus target identified by the American Diabetes Association (ADA) and the International Society for Pediatric and Adolescent Diabetes (ISPAD) (American Diabetes, 2016;Rewers et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this confluence of issues often results in deteriorating glycemic control. International data have identified significant shortfalls as only about 14% patients with T1DM aged 11-18 years actually achieve glycated hemoglobin (HbA1c) levels of b7.5% (Dunger, 2017;Maahs et al, 2014;Miller et al, 2015) which is the consensus target identified by the American Diabetes Association (ADA) and the International Society for Pediatric and Adolescent Diabetes (ISPAD) (American Diabetes, 2016;Rewers et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…26 However, such programs are not widely available, not covered by insurance, and often not accessible by the target population. 27,28 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the salient themes highlighted in this study, standardized EU-CDEC in place, first, education and training will be aligned according to evidence-based practices and current global health policy and guidelines. 12,17,[27][28][29][30] Second, clear teaching and learning pathways will be created that act as a common language, facilitating greater mobility of HCPs between countries to enhance professional experience and expertise. Third, greater quality assurance will help to increase standards among the diabetes workforce and equally, raise the profile of diabetes educators collectively.…”
Section: Interdisciplinary Work In the Diabetes Teammentioning
confidence: 99%